PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN SIMULASI VIRTUAL TERHADAP PENGUASAAN KONSEP FISIKA PESERTA DIDIK SMA - Sumarni Sumarni; Kosim Kosim; Ni Nyoman Sri Putu Verawati (Department of Physics Education, Universitas Mataram, 2020)
This study aims to determine the effect of guided inquiry learning models assisted by virtual simulations on the mastery of physics concepts for high school students. This type of research is a quasi-experimental with a pretest-posttest control group design. The study population was all students of class XI MIA SMAN 1 Sheet, totaling 53 students with the sampling technique using purposive sampling technique, so the sample used in this study was class XI MIA-2 as an experimental class totaling 26 students and class XI MIA. -3 as a control class, totaling 27 students. Before being given treatment, the two samples were given an initial test to determine their initial ability. The results show that the the ability of both class control and experiment are homogen. That meansÃÂ before doing the treatment, they have the same abilty. The research hypothesis was tested by using polled variance t-test with a significance level of 5%. Based on the results of data analysis, t count is greater than t table, so that H0 is rejected and Ha is accepted. Thus, it can be concluded that the guided inquiry learning model assisted with virtual simulations has an effect on the mastery of physics concepts for high school students.